HUMAN RIGHTS ASPECTS ON CROSS BORDER REFUGEE PROBLEMS - Romsan, Achmad (Indonesian Journal of International Law, 2010)
Currently, refugee problems are a matter for the international society. In practice, their rights are objects for violations frequently. However, as an individual, refugee has the right for protection under national law and international law. In addition, a Refugee possesses the human rights which applied generally. This article discusses refugee problems from the perspective of human rights consisted within the international conventions and national legal rules.